2007
DOI: 10.1590/s0004-27302007000700022
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre a bomba de infusão de insulina subcutânea e o esquema de múltiplas doses de insulina em adolescentes com diabetes melito do tipo 1 da rede pública de saúde na abordagem da hipoglicemia grave

Abstract: RESUMOObjetivo: Avaliação comparativa da freqüência de hipoglicemia severa após mudança da terapia com múltiplas doses de insulina (MDI) para bomba de insulina subcutânea (BIISC). Pacientes e Métodos: Sete pacientes DM1, idade Mi = 14 anos e tempo médio de diabetes de 8 anos, comparados de acordo com a incidência de hipoglicemia, a dose total de insulina (U/Kg/d), IMC (Kg/m 2 ) e HbA1c (vn: 3,5-6,7%) 1 ano antes e 1 ano após a transferência de terapêutica. Houve redução significativa dos episódios de hipoglice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Similarly to our data, a previous Brazilian study has also showed reduction of severe hypoglycemia episodes. In spite of fewer subjects and shorter period of observation, this analysis showed a little improvement of metabolic control; furthermore, the authors have not compared MDI and CITT 27. A recent paper showed in 345 patients a 0.6% reduction of HbA1c levels from injections to insulin pump therapy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly to our data, a previous Brazilian study has also showed reduction of severe hypoglycemia episodes. In spite of fewer subjects and shorter period of observation, this analysis showed a little improvement of metabolic control; furthermore, the authors have not compared MDI and CITT 27. A recent paper showed in 345 patients a 0.6% reduction of HbA1c levels from injections to insulin pump therapy.…”
Section: Discussionmentioning
confidence: 87%
“…De forma similar aos nossos dados, um estudo brasileiro anterior também mostrou redução dos episódios de hipoglicemia grave. Apesar do número menor de indivíduos e período de observação mais curto, essa análise mostrou uma pequena melhora do controle metabólico; além disso, os autores não compararam MDI e SIC 27. Um estudo recente mostrou em 345 pacientes uma redução de 0,6% dos níveis de HbA1c que mudaram do tratamento com injeções para a bomba de insulina.…”
Section: Discussionunclassified
“…In spite of fewer subjects and shorter period of observation, this analysis showed a little improvement of metabolic control; furthermore, the authors have not compared MDI and CITT. 27 A recent paper showed in 345 patients a 0.6% reduction of HbA1c levels from injections to insulin pump therapy. The authors also showed a reduction of severe hypoglycemic events and DKA episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar do número menor de indivíduos e período de observação mais curto, essa análise mostrou uma pequena melhora do controle metabólico; além disso, os autores não compararam MDI e SIC. 27 Um estudo recente mostrou em 345 pacientes uma redução de 0,6% dos níveis de HbA1c que mudaram do tratamento com injeções para a bomba de insulina. Os autores também mostraram uma redução de eventos hipoglicêmicos graves e episódios de CAD.…”
Section: Discussionunclassified